A framework for security technology cohesion in the era of the GDPR. Issue 12 (December 2018) - Wilson, Simon
Abstract : Right now, malicious actors are attempting to penetrate your organisation's network. In the UK, four out of 10 businesses have suffered a breach or attack in the past 12 months, rising to two-thirds for larger businesses. 1 The stakes have never been higher: the average total cost of a data breach in the UK is already £3.96m. 2 With the General Data Protection Regulation (GDPR) now adding considerable fines, this figure will only increase. The General Data Protection Regulation (GDPR) creates a new benchmark for personal data protection and its influence will be felt far and wide. It is now the template for privacy laws throughout the world . In addition, security and IT teams now have the opportunity to use the GDPR framework to better manage the collection and use of personal data while filling in potential gaps in their protection infrastructure. Simon Wilson of Aruba proposes a framework to ensure that attacks are dealt with in a GDPR-aware manner, minimising fines, reducing breach-related costs and ultimately better protecting information.